Enhanced Magneto-Optical Effect in Heterostructures Composed of Epsilon-Near-Zero Materials and Truncated Photonic Crystals - Hu, Shengyu; Guo, Zhiwei; Dong, Lijuan; Deng, Fusheng; Jiang, Haitao; Chen, Hong (Frontiers in Materials, 2022)
Optical non-reciprocal transmission plays an important role in many applications such as optical isolation, switching, and integrated photonic circuits. However, the non-reciprocity of natural magneto-optical (MO) materials is too weak to be widely used in the actual applications. Magnetized metamaterials enable the exploration of a new regime about the MO effect, including the enhanced non-reciprocal transmission and one-way surface waves. In this work, the Fano-type interference effect is studied in the heterostructure composed of a magnetized epsilon-near-zero material and a truncated photonic crystal. The inherent weak MO activity is significantly enhanced in the heterostructure because of the field intensity enhancement mechanism and Fano interference. The results provide a way to design novel optical non-reciprocal devices with excellent performance using metamaterials.